Fucoidan alleviates the hepatorenal syndrome through inhibition organic solute transporter α/β to reduce bile acids reabsorption - Xiaojuan Zhao; Ting Yang; Jiayan Zhou; Yanli Chen; Qian Shen; Jiankang Zhang; Qianqian Qiu (Elsevier, 2023)
The high levels of bile acids are a critical factor in hepatorenal syndrome. Organic solute transporter α/β (Ostα/β) participate in bile acids reabsorption in the kidney. Fucoidan has the great potential in protecting against liver and kidney injury. However, whether Ostα/β increase bile acids reabsorption in bile duct ligature (BDL)-induced hepatorenal syndrome and the blockade of fucoidan are still not clear. Male mice that received BDL were given to fucoidan (at 12.5, 25 and 50 ​mg/kg) through intraperitoneal injection once daily for three weeks. The serum, liver and kidney samples of these experimental mice were collected to carry out biochemical, pathological and Western blot analysis. In this study, fucoidan significantly lowered serum activities of alanine aminotransferase (ALT) and aspartate aminotransferase (AST), decreased serum levels of uric acid, creatinine and uric nitrogen, restored the deregulation of the renal urate transporter 1 (URAT1), organic anion transporter 1 (OAT1), and organic cation/carnitine transporter 1/2 (OCTN1/2), consistence with alleviation BDL-induced liver and kidney dysfunction, inflammation and fibrosis in mice. Furthermore, fucoidan significantly hampered Ostα/β and reduced bile acids reabsorption in BDL-induced mice, protected against AML12 and HK-2 ​cells injury in vitro. These results demonstrate that fucoidan alleviates BDL-induced hepatorenal syndrome through inhibition Ostα/β to reduce bile acids reabsorption in mice. Therefore, suppression of Ostα/β by fucoidan may be a novel strategy for attenuating hepatorenal syndrome.